PESTEL analysis of green tourism development based on Lumbung Mataraman: Comparative study of Bantul and Kulon Progo regencies - Unggul Priyadi; Jannahar Saddam Ash Shidiqie; Alivia Rianti Putri (Universitas Ahmad Dahlan, 2026)
Green tourism initiatives tend to prioritize physical development and agricultural outputs, while insufficient attention is given to the integration of political coordination, economic value chain strengthening, social participation, technological innovation, environmental management, and legal-institutional arrangements. As a result, the development of Lumbung Mataraman-based green tourism remains fragmented and context-dependent, limiting its capacity to function as a comprehensive and sustainable development model. Addressing this gap, this study conducts a comparative analysis of green tourism development under the Lumbung Mataraman initiative in Bantul and Kulon Progo Regencies using the PESTEL framework. A qualitative comparative approach was employed through in-depth interviews, field observations, and document analysis, with all data coded and thematically analyzed using NVivo. The results reveal contrasting development patterns: Bantul demonstrates a governance-driven model marked by cross-sectoral integration and collaborative networks, while Kulon Progo exhibits a commodity-driven model dominated by plantation-based agrotourism with limited diversification. By extending the application of PESTEL to community-based green tourism linked to food security initiatives, this study offers a comparative conceptualization of differentiated development models that can inform more context-sensitive and adaptive regional tourism policies.